Buddhist Based Management Strategies for Meditation Centers - สุภาจาโร พระครูวิวิธกาญจนคุณ; มหาเทียร จริยา (Journal of Educational Review Faculty of Education in MCU, 2018)
The management of meditation centers in Buddhism needs effective management system and not contrary to the principles of Dhamma and Vinaya. The management of meditation center for best performance and the requirements of Buddhists in Thailand depends on management system. The management strategy in the management of meditation centers requires competent executives in management to lead the centers to achievement